Dampak Kebijakan Relokasi Tempat Dagang Bagi Pedagang Keripik Belut di Pasar Godean - Rini Susilawati; Arief Budi Pratomo (Universitas Muhammadiyah Semarang, 2018)
Factors location for a business activity is one very important factor in supporting the success and continuity of business. So also for a group of craftsmen eel in Godean, Sleman. Yogyakarta is already very well known as a center of chips eel in Yogyakarta has been long sought after and visited buyer as souvenirs typical of Yogyakarta. Relocation of trade policy always have an impact that is not always positive, but sometimes negative impact as well, both for visitors, especially for merchants. This study used descriptive qualitative method. The subjects of this study is the merchant chips culinary center Eels eels in Godean, Sleman, Yogyakarta. Object of this research is the socio-economic conditions as a result of their relocation merchant market. Mechanical determination of informants using purposive sampling technique. Data collection techniques used were observation, interview, and documentation. Data analysis technique using an interactive model Huberman and Miles, (1984), namely through four processes: (1) data collection, (2) data reduction, (3) pre sentation of data, and (4) conclusion. Technique authenticity of data is done by triangulation techniques. The research data is planned in the form that will be distributed in approximately 30 merchants chips eel in the market Godean, Sleman, Yogyakarta, which is used as the respondent, from a populationof about 40 traders as a whole, whereas the technique uses accidental sampling, the choice of respondents without a planned and specific criteria, but which by chance met and deemed feasible, it is to be preferred as a sample.